Synthesis and Characterizations of Semiconductor Material (Cu2ZnSnS4) for Solar Cell - Verma, Shri Kant (My University, 2011)
Quaternary kesterite-type Cu2ZnSnS4 (CZTS) nanoparticles for low-cost thin film solar cell were successfully synthesized using a relatively simple and convenient solvothermal and hydrothermal route without and with nitrogen atmosphere. Nanoparticles with diameters of about 5–10nm were obtained at the temperature of 1800C, analyzed by transmission electron microscopy (TEM).The morphologies of the continuous CZTS films with satisfactory stoichiometry were characterized by scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDXA). The crystallinity of CZTS nanoparticles was greatly improved by annealing in H2S (5%) /Ar mixed gases analyzed by X-ray diffraction (XRD). High-resolution X-ray photo-emission spectroscopy (XPS) analysis of the four constituent elements confirmed the purity and composition of CZTS nanoparticles. UV–vis absorption spectra measurement indicated that the band gap of as-synthesised CZTS nanoparticles of both was about 1.5eV, which was near the optimum value for photovoltaic solar conversion in a single-band-gap device.
M.Tech. (Material and Metallurgical Engineering)
Keywords: Solar Cell; Semiconductor Material (Cu2ZnSnS4)